(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article analyzes the conceptual field of forming a health and recreation community for family members of combat participants. Military conflicts and their consequences have a complex negative impact on the physical and mental health of not only combatants, but also their family members, who experience significant psychological stress due to the constant unpredictability of war, physical danger and threat to life, loss and separation from loved ones, forced displacement and social isolation, economic hardship and need long-term adaptation to changed living conditions. An effective approach to mitigate such consequences is engaging family members of combatants in health and recreation communities that offer social integration, psycho-emotional support, enhancements to physical well-being, development of healthy habits, family cohesion and improvement of quality of life. This study aims to analyze the fundamental concepts surrounding health and recreation communities designed for the families of combatants. The research employs a variety of methods, including theoretical analysis of scientific literature, online information resources, and documentary materials, as well as system and comparative analysis. The research was conducted in 2024, analyzing 120 sources. The study’s results demonstrate a relationship between social support and physical activity. Health and recreation communities play a crucial role in fostering a healthy society, and their development requires a comprehensive approach that encompasses sociological, psychological, economic, and environmental aspects. It has been established that the development of such communities requires scientific justification and adaptation to Ukrainian realities, particularly in the context of socio-cultural characteristics and resource capabilities.